Analysis of Dynamics and Restructuring of PT Pertamina (Persero) - Pangestu, Ririh Aji (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2023)
Since its inception, PT Pertamina (Persero) has experienced many organizational dynamics or changes. ranging from changes in name and status, refining the vision, to restructuring the company. Through a qualitative approach by applying the literature review method, it is interesting to analyze, describe, and discuss further the dynamics or changes that occur in PT Pertamina (Persero), namely restructuring in 2018 to 2021 through the formation of a holding company, as well as the implications in relation to company performance. As a result, it appears that the holding-sub-holding framework as a form of restructuring is an appropriate choice taken by the Indonesian government (as a shareholder) in connection with a series of positive results (in the form of profit optimization and operational cost efficiency) that are quite significant. Because of restructuring, the organizational or operational structure of PT Pertamina (Persero), which was originally so fat and large, resulting in a slow decision-making process, has become lean. This has good implications for the company, which has become faster, more agile and concise in the decision-making process. In addition, there is clarity of authority between PT Pertamina (Persero) as a holding company and its sub-holdings.